THE ROLE OF COMMERCIAL REVENUES AND MEDIA BROADCASTING RIGHTS IN FINANCING THE IRAQI OLYMPIC COMMITTEE - Hussein Karim Hassoun (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. The committee works to sponsor the civil sports movement, consolidate the principles of the International Olympic Committee, and organize sports courses at the Olympic, International, Continental, Arab and regional levels. The committee also contributes to supporting various sports federations financially, morally and technically, in order to enable them to perform their mission optimally. Objectives. This research aims to identify the role of commercial revenues and media broadcasting in financing the Iraqi Olympic Committee. Method. The descriptive approach with questionnaires was used as the main data collection tool. The research sample included 232 members of the Iraqi Olympic Committee (Board of Directors, financial and media departments), heads and representatives of Olympic sports federations, employees of financial and marketing departments in sports institutions, sports media experts and sports broadcast analysts, sports marketing and sponsorship officials in sponsoring companies or interested in sports investment, and academics specializing in sports management or sports economics. Results. The results showed that the quality of media coverage affects the level of business partnerships, the committee also suffers from poor relations with major media outlets, and the local market lacks a culture of investing in sports. Conclusion. The researcher recommended the need to strengthen relations with major media outlets to increase media coverage, support business partnerships, and develop a culture of investment in sports within the local market through awareness and training programs.